The importance of contextual, relational and cognitive factors for novice nurses’ emotional state and affective commitment to the profession. A multilevel study - Hoeve, Yvonne ten; Brouwer, Jasperina; Roodbol, Petrie F.; Kunnen, Saskia (Journal of advanced nursing, 2018)
Aim This study explored the effects of contextual, relational and cognitive factors derived from novice nurses’ work experiences on emotions and affective commitment to the profession. Background With an increasing demand for well‐trained nurses, it is imperative to investigate which work‐related factors most affect their commitment to develop effective strategies to improve work conditions, work satisfaction and emotional attachment. Design A repeated measures within subjects design. Methods From September 2013–September 2014 eighteen novice nurses described work‐related experiences in unstructured diaries and scored their emotional state and affective commitment on a scale. The themes that emerged from the 18 diaries (with 580 diary entries) were quantified as contextual, relational and cognitive factors. Contextual factors refer to complexity of care and existential events; relational factors to experiences with patients, support from colleagues, supervisors and physicians; cognitive factors to nurses’ perceived competence. Results The first multilevel regression analysis, based on the 18 diaries with 580 entries, showed that complexity of care, lack of support and lack of competence were negatively related to novice nurses’ affective commitment, whereas received support was positively related. The next multilevel regression analyses showed that all contextual, relational and cognitive factors were either related to negative or positive emotions. Conclusion To retain novice nurses in the profession, it is important to provide support and feedback. This enables novice nurses to deal with the complexity of care and feelings of incompetence and to develop a professional commitment.